The STAT5b Pathway Defect and Autoimmunity - Kanai, Takahiro; Jenks, Jennifer; nadeau, Kari C. (Frontiers in Immunology, 2012)
The signal transducer and activator of transcription (STAT) 5b is a universal transcription factor that plays key biological roles in allergic diseases, immunodeficiencies, autoimmunities, cancers, hematological diseases, growth disorders, and lung diseases. The identification of distinct pathological manifestations of STAT5b deficiency in humans has highlighted the critical role of the STAT5b pathway. Proper gene transcription at IL-2Ra, FOXP3, Bcl-2, and growth hormone associated loci are thought to be associated with normal STAT5b transcriptional activity. These genes are thought to play important roles in allergy/autoimmunity, immunodeficiency, cancer/anemia, and growth, respectively. The STAT5A and STAT5B genes are collocated on 17q21. Although these two monomeric proteins exhibit peptide sequence similarities of >90%, it is known through observations of STAT5b deficient subjects that STAT5a and STAT5b are not fully redundant in humans. Patients with STAT5b deficiency have decreased numbers of regulatory CD4+CD25high T cell (Treg) despite their STAT5a levels being normal. Prior studies on STAT5b deficient subjects have revealed immunological aberrations associated with the following disease phenotype: modest lymphopenia and decreased populations of Treg, γ-δ T cells, and natural killer (NK) cells. Most subjects with STAT5b deficiency show severe eczema, and autoimmune disease (juvenile idiopathic arthritis, autoimmune thyroiditis, idiopathic thrombocytic purpura) which are thought to be associated with Treg dysfunction. We will review the likely pathophysiological mechanisms associated with STAT5b deficiency.